Atrazine and Methyl viologen effects on Chlorophyll-a fluorescence revisited. Implications in Photosystems Emission and Ecotoxicity Assessment - Iriel, Analia (2014)
In this work, we use the effect of herbicides that affect the photosynthetic chain at dened sites in the photosynthetic reaction steps to derive information about the uorescence emission of photosystems. The interpretation of spectral data from treated and control plants, after correction for light reabsorption processes, allowed us to elucidate current controversies in the subject. Results were compatible with the fact that a nonnegligible Photosystem I contribution to chlorophyll uorescence in plants at room temperature does exist. In another aspect, variable and nonvariable chlorophyll uorescence were comparatively tested as bioindicators for detection of both herbicides in aquatic environment. Both methodologies were appropriate tools for this purpose. However, they showed better sensitivity for pollutants disconnecting Photosystem II?Photosystem I by blocking the electron transport between them as Atrazine. Specically, changes in the (experimental and corrected by light reabsorption) red to far red uorescence ratio, in the maximum photochemical quantum yield and in the quantum efciency of Photosytem II for increasing concentrations of herbicides have been measured and compared. The most sensitive bioindicator for both herbicides was the quantum efciency of Photosystem II.